"Do I really need it?": An explorative study of acceptance and usage of in-vehicle technology. (January 2022) - Stiegemeier, Dina; Bringeland, Sabrina; Kraus, Johannes; Baumann, Martin
Highlights: Drivers use on average 70% of available in-vehicle systems regularly. Reasons not to use in-vehicle technology were investigated exploratively. Frequent reasons are need, context and task, and preference for own action. An Integrated Acceptance Model (IAM) is introduced. Abstract: The vehicle is increasingly equipped with additional technology assisting and entertaining the driver. To improve the systems and increase their usage, it is important to understand what influences the acceptance of technology in the vehicle. An online survey was conducted assessing which systems drivers own and use in their vehicles today. For the equipped systems, the reasons why N  = 304 drivers do not use their in-vehicle technology were qualitatively explored. An inductive content analysis revealed 13 categories in total. The three categories "Need", "Context and Task", and "Reliability" were associated with Perceived Usefulness while "Increased Effort" and "Aversion" were associated with Perceived Ease of Use (Venkatesh, 2000). In addition, the influencing factors are further extended with the "Preference for Own Action", "Distrust", "Safety", "Knowledge", and "Habit". The findings reveal subjectively important antecedents of the acceptance of in-vehicle technology and provide new insights, especially on usage barriers. An Integrated Acceptance Model (IAM) is derived from the identified categories to inform future research and facilitate a holistic view on factors influencing technology acceptance.